VARIATION OF PEAK EXPIRATORY FLOW RATE WITH BODY MASS INDEX IN THE FIRST YEAR MALE MEDICAL STUDENTS OF VISWABHARATHI MEDICAL COLLEGE, KURNOOL - BV, Surendra; Rani V, Shobha (International Journal of Clinical and Biomedical Research, 2017)
Background: Obesity has become one of the major health issues in India. WHO defines obesity as â€œA condition with excessive fat accumulation in the body to the extent that the health and wellbeing are adversely affectedâ€. Obesity results from a complex interaction of genetic, behavioral, environmental and socioeconomic factors causing an imbalance in energy production and expenditure. Peak expiratory flow rate is the maximum rate of airflow that can be generated during forced expiratory maneuver starting from total lung capacity. The simplicity of the method is its main advantage. It is measured by using a standard Wright Peak Flow Meter or mini Wright Meter. The pulmonary disorders due to obesity results in increased mortality and morbidity. Aims: To study the effect of Body Mass Index on Peak Expiratory Flow Rate in Medical students. Methods & Methods: study was performed on 60 Male age group of 17-22 Years, categorized as normal Weight BMI= 18.5-24.99kg/m2 and overweight BMI= 25-29.99 Kg/m2. ThereÂ were 30 students with normal Weight BMI and 30 students with overweight BMI. Normal weight BMI subjects acted as control group to compare the Peak Expiratory Flow Rate with over weight. The parameters studied were weight, height, age, body mass index and Peak expiratory flow rate (PEFR). Studentâ€™s unpaired t-test was used for two groupâ€™s comparison. Results: The results of the investigation revealed a significantly lower Peak expiratory flow rate (PEFR) among the overweight BMI subjects compared to normal weight BMI subjects. Conclusion: Thus it is evident from the present study that obesity significantly affects the pulmonary functions which may give rise to long term complications and may lead to early morbidity and mortality. Key words:Â Peak Expiratory Flow Rate; Body Mass Index; Obesity.